School health, nutrition and education for all : levelling the playing field - Jukes, Matthew C. H., (CABI, 2008)
This book contains 7 chapters. The following topics are discussed: case for school health and nutrition; challenges for child health and nutrition (infectious diseases and nutritional deficiencies); health, nutrition and access to education; long-term effects of preschool health and nutrition on educational achievement; health, nutrition and educational achievement of school age children; costs and benefits of school health and nutrition interventions; and school health and nutrition programmes.